Pengaruh Metode Pembelajaran Discovery Learning Berbantuan Media Audio Visual Terhadap Hasil Belajar Siswa Akuntansi: (Studi Kasus Pada SMK Negeri 1 Tejakula, Kabupaten Buleleng) - Wahyuni, Putu; Indrayani, Luh (Universitas Pendidikan Ganesha, 2023)
This study aims to determine the effect of the discovery learning method assisted by audio-visual media on the learning outcomes of accounting students at SMK Negeri 1 Tejakula. This research uses a quasi-experimental design. The subjects in this study were students of class X Accounting 1 and X Accounting 2, while the objects in this study were learning outcomes and the discovery learning method assisted by audio-visual media. This research design uses a pretest-posttest control group design. The results showed that there was an effect of using the discovery learning method assisted by audio-visual media on the learning outcomes of accounting students at SMK Negeri 1 Tejakula. The results of the t-test analysis show the t-value of 5.013 with a significance value of 0.040 < 0.05, so H0 was rejected and Ha could be accepted.